(untitled) (Panacea Journal of Medical Sciences, 2024)
Background and Objectives: Chronic renal failure affects almost all the vital organs of the body. Most CRF patients will have sensorineural hearing loss when they first report. Hemodialysis and transplantation are used to treat an increasing CRF patients; many of these individuals also require ototoxic medications. The study’s primary goal is to assess cochlear function impairment related to CRF. Materials and Methods: We studied30 patients of CRF attending our institution for a period of 2 years, from September 2020 to august 2022. All patients were evaluated for hearing loss. We found hearing loss in 17 patients, and 13 patients did not show any hearing loss. Result: 17 patients showed hearing loss at various frequencies, and 13 were normal. 5 showed a loss in low, 10 in mid, and 17 in high frequency. The HL group had low levels of serum sodium level (125.8 mmol/dl) compared to the non-HL group (141.4 mmol/dl). We found that the HL group had a higher percentage of taking ototoxic drugs in 9 patients (52.9%). Only two (15.4%) of the non-HL group had a history of ototoxicity. Conclusion: Our study shows that patients with CRF have sensorineural hearing loss. Age, the duration of CRF, the period of hemodialysis, the use of ototoxic medications, blood urea levels, serum creatinine, and serum sodium all showed positive correlations with hearing loss. To stop further deterioration, physicians must be aware of this and take precautions to avoid potential ototoxic substances, loud exposure, hypotension, and other abrupt changes during hemodialysis.